Robotic natural orifice transluminal endoscopic surgery (R-NOTES): Literature review and prototype system. Issue 1 (March 2015) - Azizi Koutenaei, Bamshad; Wilson, Emmanuel; Monfaredi, Reza; Peters, Craig; Kronreif, Gernot; Cleary, Kevin
Abstract In minimally invasive surgery methods such as laparoscopic surgery, surgical instruments are introduced through small incisions to minimize patient trauma and recovery times. To reduce the number of incisions, new techniques such as natural orifice transluminal endoscopic surgery (NOTES) have been proposed. Compared to laparoscopic surgery, the NOTES approach, which requires new technology and improved instruments, presents some unique challenges. Robotic NOTES (R-NOTES) could be an enabling technology for these procedures. In this paper, we first review relevant work in R-NOTES. We then present our work and the system architecture for an R-NOTES prototype system incorporating wireless command and control. The system was tested twice in swine animal studies.